Investigating the melting behaviour of polymorphic zeolitic imidazolate frameworks. Issue 21 (15th May 2020) - Bumstead, Alice M.; Ríos Gómez, María Laura; Thorne, Michael F.; Sapnik, Adam F.; Longley, Louis; Tuffnell, Joshua M.; Keeble, Dean S.; Keen, David A.; Bennett, Thomas D.
Abstract : The study of polymorphic zeolitic imidazolate frameworks demonstrates the influence of linker chemistry and framework structure on their thermal behaviour. Abstract : Recently, there has been growing interest in the amorphous states of metal–organic frameworks (MOFs). Particular focus has been given to melt-quenched MOF glasses. In this work, to improve our understanding of the factors influencing melting, the thermal response of four closely related zeolitic imidazolate frameworks (ZIFs) was studied. Electron withdrawing ligands were found to lower both the melting and glass transition temperatures, providing a promising strategy for improving the processability of MOFs in the liquid state. Crucially, dense frameworks appear to be essential for melting, with their presence also initiating the melting of open pore frameworks. This opens up the rich polymorphic landscape of ZIFs to the preparation of novel MOF liquids and glasses.